2009
DOI: 10.1248/cpb.57.657
|View full text |Cite
|
Sign up to set email alerts
|

Particle Characterization of Poorly Water-Soluble Drugs Using a Spray Freeze Drying Technique

Abstract: 657Many newly developing compounds have been dropped out during the early stages of drug development process because of poorly water-soluble property. Poorly water-soluble drugs often demonstrate the low bioavailability when administered orally due to the low dissolution and absorption rate in the gastrointestinal tract. Therefore, improvement of the solubility of poorly water-soluble compounds is an important mission in drug development.Increasing the solubility and dissolution rate of poorly water-soluble dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 15 publications
1
14
0
10
Order By: Relevance
“…It was found that 4N-SFD-MeCN particles (B-1, 2, 3) have porous and spherical structure, which is same characteristic morphology exhibited in 4N-SFD-aqua particles (A-1, 2, 3) as also reported in previous paper. 20,21) No difference in particle size was visually confirmed and Phe : Eud-L particles from both systems had 2-25 mm in diameter as shown in low-magnified photographs (A-3, B-3). However, the size and quantity of pores observed in the 4N-SFD-MeCN particles (B) are apparently smaller than those of 4N-SFD-aqua particles (A).…”
Section: Morphological Analysis Of Sfd Composite Particlesmentioning
confidence: 87%
See 2 more Smart Citations
“…It was found that 4N-SFD-MeCN particles (B-1, 2, 3) have porous and spherical structure, which is same characteristic morphology exhibited in 4N-SFD-aqua particles (A-1, 2, 3) as also reported in previous paper. 20,21) No difference in particle size was visually confirmed and Phe : Eud-L particles from both systems had 2-25 mm in diameter as shown in low-magnified photographs (A-3, B-3). However, the size and quantity of pores observed in the 4N-SFD-MeCN particles (B) are apparently smaller than those of 4N-SFD-aqua particles (A).…”
Section: Morphological Analysis Of Sfd Composite Particlesmentioning
confidence: 87%
“…The resultant spray freeze-dried (SFD) composite particles were collected and stored in glass vials in a desiccator at room temperature before the characterization measurement. The detailed operational conditions of SFD preparation were basically same as those of previous experiments 20) except freeze-drying equipment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, numerous approaches have been made to improve aqueous solubility of poorly soluble drugs in pharmaceutical industry and science. Most of strategies are based on particulating the drugs in small scale (nano-or micro-scale) through milling (Remenar et al, 2003;Choi et al, 2004;Hu et al, 2004), spray drying (Hu et al, 2004;Kondo et al, 2009) and nanoemulsification (Shakeel and Faisal, 2009) to increase the surface area-to-volume ratio of drug particles themselves, hence better interaction with the surrounding aqueous media. Many different types of delivery vehicles were also introduced to improve drug solubility, the approach of which was basically similar as distributing drug particles of small size inside of delivery vehicles (Chung et al, 2003;Denga et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Adjusting the solid content did not affect the size distribution, probably because the viscosity of dispersion was not affected by the different solid content. 33 The hypothetical mechanism for microsphere formation is illustrated in Figure 2. After spraying, the surface water of microbeads may quickly evaporate, which gives rise to the skin layer, in particular at high solid contents.…”
Section: Discussionmentioning
confidence: 99%